Military School in Misrata and its role in the Libyan Jihad movement 1916-1922 - Amima, Fathi; Mahmoud, Abdul Hakim ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2020)
Despite the economic conditions that the Libyan people had been experiencing before and during the Italian occupation, they managed to courageously resist the occupier and stable during which the Mujahideen developed their fighting skills to confront an enemy that outnumbered them in men and equipment. The struggle was according to military programs and plans, from which the Military School was established in Misurata in 1916 to 1922 AD. The research starts from a complex study regarding the difficult conditions that the Libyans were living in, and their drive to defend the homeland did not stop without their attempt to free this country from the clutches of the colonialist. Thus, a war college was established to prepare fighters according to scientific foundations. How was this done? What is the role that this institution provides for the jihad movement? The research referred to the location of the school and the reasons for its selection. There were major discussions about the strength of the Mujahideen, the management of the school and the study system, and its role in the movement of jihad, and a conclusion that included a number of results.